Feasibility Assessment of Microgrid Wind Energy Systems: Implementation of TASED in the Arctic Regions of Yamal and Murmansk - Karnaukhov, Ilya; Maksimov, Lev; Baker, Rowan; Najafabadi, Milad Y. (Stanford U.S. -Russia Forum Journal, 2020)
Due to its extreme climate and low population density, the Russian Arctic region remains largely infrastructurally undeveloped. Many settlements in the Arctic area are not connected to the Unified Energy System of Russia (UES) and employ various carbon-intensive sources for local electricity generation. Currently, the Russian government has drafted a strategic development plan for the region, specifically utilizing the region's vast supply of oil and natural gas reserves for electricity generation. The Arctic ecosystem is fragile, and constructing new oil, gas, or diesel power stations may not be sustainable for the region. Additionally, the utilization of fossil fuels would exclude the current technological advancements in electricity systems. This paper offers an improved and more sustainable approach to developing electricity generation in remote localities. Given unique regional ecological and sustainability concerns, Territories of Advanced Social and Economic Development (TASED) should be created in the Arctic regions of Yamal and Murmansk in order to integrate wind electricity generation on a small scale in these regions' most remote population centers. Not only would this protect the region's ecosystem from the negative effects of new fossil fuel power stations, but it would also present new opportunities for equitable development of the region's economy.